A Systematic Review on Cross-Cultural Comparative Studies of Sleep in Young Populations: The Roles of Cultural Factors - Jeon, Mina (Int J Environ Res Public Health, 2021)
Recent studies have shown that sleep is influenced and shaped by cultural factors, including cultural values, beliefs and practices. However, a systematic understanding of how cultural factors in countries may influence sleep duration and sleep disturbances is still lacking. Therefore, we focused on a comparison of sleep duration and disturbances in young populations between countries. We report cross-cultural differences between the child, parent and environmental factors, and their association with sleep duration and disturbances. The review is based on literature searches of seven databases published until December 2020. Studies were included if they investigated sleep duration and disturbances of individuals up to 18 years across at least two or more countries. The results of this review have shown that sleep duration and disturbances vary between countries and regions and certain factors (e.g., bedtime routines, sleeping arrangement, physical activity and psychological functioning) have been associated with sleep duration or disturbances. This review also demonstrates that certain factors which were associated with sleep duration or disturbances in one country, were not shown in other countries, suggesting a need for recommendations for age-related sleep duration and sleep interventions to consider cultural differences that influence sleep duration or disturbances in individual countries or regions.